Estimation of stress intensity factor reduction for a center-cracked plate integrated with piezoelectric actuator and composite patch - Abdul, Abid; Hrairi, Meftah; Abuzaid, Ahmed; Mohamed Ali, Jaffar Syed (Elsevier, 2021)
Active repair of a damaged structure using piezoelectric (PZT) actuators has played a significant role during the last two decades in reducing crack damage propagation in structures due to its electro-mechanical effect. Similarly, passive repair of damaged structures using composite materials has been widely used in recent years, and it has been divided into many types. In this paper, the hybrid repair of center-cracked plate using PZT actuators at the front of a plate and a composite patch at the back of the plate is analytically and numerically investigated. First, the solution is obtained from Rose’s equations for the center-cracked plate integrated with a composite patch and a passive PZT actuator under uniform uniaxial load. Second, the stress intensity factor (SIF) for a center-cracked plate due to stress produced by a PZT actuator is analytically modeled using the weight functions method. The superposition principle is then used to superimpose the aforementioned solutions in order to yield the PZT actuator and composite patch’s hybrid stress intensity factor for the center-cracked plate. Finally, the proposed analytical method was verified using the finite element method. The results demonstrate low relative errors between the analytical and the FE of below 5% in all the cases studied in this paper.